A representação da morte em Paripiranga – Bahia : ritos, práticas e discursos (1919 – 1961) - Santos Junior, Robério José (2021)
The present work analyzes the representation of death in Paripiranga-Bahia between the decades of 1919 to 1961, bringing up the main events that were directly or indirectly linked to death. A priori, it was possible to understand the main facts that marked the initial formation of the city, highlighting the character of Father João de Matos Freire de Carvalho, as well as the entire process of building a new cemetery for the site, meeting the desires of the new hygienist laws. from Europe, which gained strength in Brazil in the first decades of the twentieth century. Then, I present the funeral representations in the speeches produced by the press men who worked at the newspaper O Paladino (1919-1938), observing, above all, the obituary notes and the annunciations focused on the subject in question. Finally, I examine the role of the newspaper O Ideal for the realization of new funeral practices in the city of Paripiranga-Bahia (1953-1961), listing the trajectory of the periodical as an important means of social communication, the criticisms printed and the chronicles of the day of the dead. Thus understanding that it was not only Father João de Matos and the Catholic Church who were solely responsible for matters related to death. But that also, newspapers and pressmen contributed in this social and religious context.